3, 2, 1 ao vivo! Disfluências e refazimentos em interpretação de conferência remota de Libras para português - Ribeiro, Nadia Maria Fonseca Campos (2024)
This research has the general objective of indicating the occurrences of disfluencies and repairs in interpretation into the Portuguese language, typical or common, identified from a real, uncontrolled situation of an on-line, simultaneous, intermodal and remote conference interpretation. Unfolding into reflections on the challenges of intermodal interpretation (Libras-Portuguese) at an academic level in the context of conferences and on the expertise required of Libras-Portuguese Interpreter Translators in Higher Education Institutions (TILSPIES) to meet the requirements of the Portuguese language at the academic level, based on the Cavallo model (2022) and as a support and preparation tool, it proposes the creation of an Interpretation Charge model. To this end, we seek to base ourselves on the concepts of Functionalist Theory (NORD, 1991; 2016), bringing reflections on intermodal translation competence (RODRIGUES, 2018), seminal contributions to the investigation of intermodal conference interpretation and post-pandemic challenges ( NOGUEIRA 2016; 2019; 2022), the competence of the Interpreter and his proposed competence model for the conference interpreter (CAVALLO 2019; 2022), concepts of common disfluencies in speech and interpretation (VISCH; 2017, COLLARD; DEFRANCQ, 2019; GOSY 2007; DEFINO E MAGALHÃES, 2010; MACGREGOR, 2008; ZHAO N., 2022; TISSI, 2000; BAKTI, 2009; PÖCHHACKER, 1995; BENDAZZOLI ET AL 2011; DAYTER 2021; ARNONE, 2018; LEMOS E RODRIGUES, 2021) A research methodology has a qualitative approach and uses as a data collection method documentary research of works carried out in the period from 2003 to 2022, and for analysis, the self-confrontation of the interpretative task of an academic event hosted on the YouTube platform, in which they appeared three sign languages and one vocal language simultaneously. Data analysis points to the phenomenon of environmental issues and the Interpreter's experience that can result in disfluencies in the interpretation of the type: Filled Pauses, Lexical Fillers, Silent Pauses (space between the reparandum and the reparatum), Prolongations, Error, Repetitions, False Starts, Truncated Words or Sentences, Repetitions, Repairs, Sliding, Vocalized Hesitations, Stretching, Change in Voice Quality, TOT, Restructuring and Anaphorism.